Knowledge, Attitude and Practice Towards Covid 19 Vaccine Among Pregnant Females in Makkah Region: Pharmaceutical Science-Pharma - Alsaadi, Farah; H. Falemban, Alaa; M. Alsanosi, Safaa; Bukhary, Deena; Al-Hindi, Yosra (International Journal of Life Science and Pharma Research, 2022)
Coronavirus disease 2019 (COVID-19) is an emerging respiratory disease that is caused by a novel coronavirus, which was first diagnosed in December 2019 in Wuhan, China, and subsequently spread to many other countries. Numerous countries have reported increasing numbers of confirmed cases and death per day; therefore, on March 11, 2020, the WHO declared COVID-19 a pandemic. COVID-19 is a highly infectious disease and can affect patients with low immunity especially pregnant females. Vaccines are an important source of elevating immunity and promoting health. Our main aim for this study is to determine the knowledge, attitude, and practice of pregnant females towards COVID-19 vaccine in Makkah Mukarramah. A cross-sectional survey was carried out among 73 consenting pregnant women using pretested questionnaires. In our results we found the mean age and mean gestational age of the respondents were between 25 and 30 years of age and third trimesters, respectively. More than four-fifths (90%) of the females believed that COVID-19 is real, and their main source of information was the internet. The majority had adequate knowledge of COVID-19. Majority showed a good attitude and preventive practice of COVID-19 disease; however, 39 percent thought that hospitals are very infected with this virus. The study population has good knowledge, attitude, and practice of COVID-19 disease and the need of vaccination against it. However, community education is needed to reduce anxiety among pregnant women and to increase the acceptance of vaccination towards improving health and immunity. Key words: , , , , ,